Human factors analysis of China's confined space operation accidents from 2008 to 2018. (July 2021) - Xia, Jingjing; Liu, Yi; Zhao, Dongfeng; Tian, Yue; Li, Jianguo; Zhong, Yufa; Roy, Nitin
Abstract: In recent years, several accidents in confined spaces have threatened the safety of staff and property in industries. A statistical analysis of 120 fatal accidents involving confined space operations in China from 2008 to 2018 was conducted in this study. The causes and characteristics of confined space operations accidents (CSOAs) were summarized. Focusing on the impact of human factors on CSOAs, the HFACS-MCS (HFACS-Modified Confined Space Accident) model, which consists of 5 levels and 21 factors, was established based on HFACS (Human Factors Analysis and Classification System). The chi-square (χ2) test and the OR analysis were implemented to analyze the statistically significant correlations between adjacent levels in the model. Finally, three human influence paths in CSOAs were derived. The results show that inadequate safety culture, organizational process vulnerability, inadequate supervision, supervisory violations, decision errors, and operational violations are the principal causes of the accidents. Besides, hurried and ad hoc rescue often caused more casualties. The targeted pre-accident prevention and post-accident emergency rescue countermeasures are proposed to prevent the recurrence of CSOAs and secondary accidents. Highlights: The statistical analysis of confined space accidents causes was conducted. A human factors analysis model of confined space accidents was established. The human influence paths of operation accidents in confined space were obtained. Targeted personnel and organizational management measures were proposed.